Justice as a virtue : a Thomistic perspective - Porter, Jean, 1955- (Grand Rapids, William B. Eerdmans Publishing Company, 2016)
Thomas Aquinas, says Jean Porter, "gets justice right." In this book she shows that Aquinas offers a cogent and illuminating account of justice as a personal virtue rather than predominantly a virtue of social institutions. For Aquinas, justice is more about interpersonal morality than civic or social obligations, and Porter masterfully draws out the contemporary significance of Aquinas's perspective. - back of book.
Justice as a virtue -- Virtues and vices of the will -- Justice as a moral ideal -- From ideal to law -- The perfections of the will.
Includes bibliographical references (pages 274-281) and indexes.
Keywords: Thomas, -- Aquinas, Saint, -- 1225?-1274.; Justice (Virtue); Virtues